The Emerging Alcoholic Liver Disease in China - Gao, MD, Yanhang; Gao, MD, Bin; Niu, MD, Junqi (North American Journal of Medicine and Science, 2016)
Over the past a few decades, the pattern of liver diseases in China has been changing. Alcohol abuse is a significant contributor to the global burden of disease and a leading cause of liver disease. Alcoholic liver disease(ALD) is associated with significant morbidity and mortality, which includes a spectrum of disorders from simple steatosis to steatohepatitis, fibrosis, cirrhosis and hepatocellular carcinoma. In China, with the establishment and effective implementation of the Expanded Program on Immunization for HBV from 1992, the number of newly HBV-infected patients had a significant decline; whereas the number of patients with alcoholic and nonalcoholic fatty liver diseases is growing. The incidence of ALD will continue to upsurge in China. Due to significant differences in alcohol metabolism, genetics, drinking patterns, and eating habits and behaviors between the East and the West, the pathogenesis of ALD in Chinese population may be different from the well-characterized ALD in Western countries. In this article, we reviewed and discussed the epidemic trend, the occurrence and the development of ALD in China. [N A J Med Sci. 2016;9(2):55-58. DOI: 10.7156/najms.2016.0902055]